Comparing job satisfaction among lecturers in public and non-public universities: Insights from Vietnam - Phuong Huu Tung (Journal of State Management, 2024)
This research examines job satisfaction among lecturers at public universities in Vietnam and compares it with that of lecturers at non-public universities. The findings reveal that salary, job nature, development opportunities, recognition, relationships, environment, and working conditions significantly influence job satisfaction. However, the impact of these factors varies between public and non-public university lecturers. The study underscores that lecturers’ job satisfaction is crucial for university success, influencing the quality of tertiary education and fostering innovation.